Leadership Communication Strategy in The Leadership Administration Bureau of The Regional Secretariat of Southeast Sulawesi Province in Improving Employee Performance - Safarudin Safarudin; Abdul Razak; Ummy Kalsum (PT. Hafasy Dwi Nawasena, 2025)
This study aims to evaluate and analyze the communication strategies of leaders in the Leadership Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province in improving employee performance. Effective leadership communication strategies are considered crucial in creating a productive and efficient work environment. The methodology used in this study included in-depth interviews with employees in the Adpim Bureau to obtain their views on various aspects of leadership communication, including audience identification, message development, method selection, and communication media use. The results of this study indicate that leaders at the Bureau of Adpim of the Regional Secretariat of Southeast Sulawesi Province actively implement communication strategies involving the use of various communication media, such as face-to-face meetings and digital messaging, to ensure clarity of information. Leaders also emphasize the importance of direct feedback and personal interaction to improve employee understanding and performance. This study identified that clear and structured communication contributes significantly to improving employee performance by reducing misunderstandings and facilitating effective task delivery. The conclusions of this study confirm that communication strategies implemented by leaders significantly influence work productivity and efficiency. This study recommends further research to explore leaders' communication styles, conflict management strategies, optimization of communication media, support for employee career development, and improved performance evaluation practices. These findings are expected to provide guidance for leaders at the Bureau of Adpim and similar organizations in designing more effective communication strategies to improve employee performance